Polymeric Nanoparticles of Pistacia lentiscus var. chia Essential Oil for Cutaneous Applications - Ilianna Vrouvaki; Eleni Koutra; Michael Kornaros; Konstantinos Avgoustakis; Fotini N. Lamari; Sophia Hatziantoniou (Pharmaceutics, 2020)
Polymeric nanoparticles (NPs) encapsulating Pistacia lentiscus L. var. chia essential oil (EO) were prepared by a solvent evaporation method, in order to obtain a novel carrier for administration on the skin. The specific EO exhibits antimicrobial and anti-inflammatory properties thus stimulating considerable interest as a novel agent for the treatment of minor skin inflammations. The incorporation into nanoparticles could overcome the administration limitations that inserts the nature of the EO. Nanoparticles were prepared, utilizing poly(lactic acid) (PLA) as shell material, due to its biocompatibility and biodegradability, while the influence of surfactant type on NPs properties was examined. Two surfactants were selected, namely poly(vinyl alcohol) (PVA) and lecithin (LEC) and NPs’ physicochemical characteristics i.e. size, polydispersity index (PdI) and ζ-potential were determined, not indicating significant differences (p > 0.05) between PLA/PVA-NPs (239.9 nm, 0.081, -29.1 mV) and PLA/LEC-NPs (286.1 nm, 0.167, −34.5 mV). However, encapsulation efficiency (%EE) measured by GC-MS, was clearly higher for PLA/PVA-NPs than PLA/LEC-NPs (37.45% vs. 9.15%, respectively). Moreover PLA/PVA-NPs remained stable over a period of 60 days. The in vitro release study indicated gradual release of the EO from PLA/PVA-NPs and more immediate from PLA/LEC-NPs. The above findings, in addition to the SEM images of the particles propose a potential structure of nanocapsules for PLA/PVA-NPs, where shell material is mainly consisted of PLA, enclosing the EO in the core. However, this does not seem to be the case for PLA/LEC-NPs, as the results indicated low EO content, rapid release and a considerable percentage of humidity detected by SEM. Furthermore, the Minimum Inhibitory Concentration (MIC) of the EO was determined against Escherichia coli and Bacillus subtilis, while NPs, however did not exhibit considerable activity in the concentration range applied. In conclusion, the surfactant selection may modify the release of EO incorporated in NPs for topical application allowing its action without interfering to the physiological skin microbiota.